2023
DOI: 10.1084/jem.20212276
|View full text |Cite
|
Sign up to set email alerts
|

Human RELA dominant-negative mutations underlie type I interferonopathy with autoinflammation and autoimmunity

Abstract: Inborn errors of the NF-κB pathways underlie various clinical phenotypes in humans. Heterozygous germline loss-of-expression and loss-of-function mutations in RELA underlie RELA haploinsufficiency, which results in TNF-dependent chronic mucocutaneous ulceration and autoimmune hematological disorders. We here report six patients from five families with additional autoinflammatory and autoimmune manifestations. These patients are heterozygous for RELA mutations, all of which are in the 3′ segment of the gene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
2
1
Order By: Relevance
“…As type I and type II IFN signaling impact T-cell function ( 23 25 ), this crosstalk may have consequences on the outcome of pathological conditions. This conclusion is in stark contrast to the observations made in patients with germline RELA haplo-insufficiency (loss-of-function mutations), who suffer from various autoimmune or inflammatory conditions and are characterized by enhanced IFNs and ISG expression ( 13 15 ). This suggests that these phenotypes mostly relied on CD8+T-cell extrinsic functions of RELA .…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…As type I and type II IFN signaling impact T-cell function ( 23 25 ), this crosstalk may have consequences on the outcome of pathological conditions. This conclusion is in stark contrast to the observations made in patients with germline RELA haplo-insufficiency (loss-of-function mutations), who suffer from various autoimmune or inflammatory conditions and are characterized by enhanced IFNs and ISG expression ( 13 15 ). This suggests that these phenotypes mostly relied on CD8+T-cell extrinsic functions of RELA .…”
Section: Discussioncontrasting
confidence: 87%
“…Consistent with mouse cells, enrichment analyses on down-regulated genes showed that RELA governed, in human CD8 + T cells, the expression of genes associated with the NF-κB pathway (NF-κB subunits and negative regulators of the pathway), markers of function, and cytokines, especially the response to type I and type III IFNs ( Figures 4D, E ). Thus, RELA controlled different aspects of human CD8 + T cell biology, suggesting a CD8 + T-cell-intrinsic role for RELA in the immunodeficiency features detected in patients with RELA LOF ( 13 15 ). After 4 days of stimulation with anti-CD3/28, a similar level of proliferation was observed in control and RELA -deficient cells, in accordance with our data from mouse experiments ( Figure 4F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a novel interferonopathy was discovered, where deletions of the 3' end of the RELA (also known as p65 in the NF-kB pathway) mRNA cause a dominant negative effect on the gene product 15 . Autoinflammation and autoimmunity in these patients was driven by an upregulation of TLR7 and MyD88 transcripts in pDCs, but also in classical and nonclassical monocytes and in myeloid DCs (mDCs).…”
Section: Figurementioning
confidence: 99%